2020
DOI: 10.1063/5.0011875
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial L1-FeNi films with high degree of order and large uniaxial magnetic anisotropy fabricated by denitriding FeNiN films

Abstract: L1 0 -orderd FeNi alloy films with a high degree of order (S) and a large uniaxial magnetic anisotropy energy (K u ) were realized by denitriding FeNiN films. FeNiN films with the a-axis perpendicular to the film plane were epitaxially grown on SrTiO 3 (001) substrates by molecular beam epitaxy by changing the growth temperatures (T S ) to 200, 250, and 350 C. The a-axis oriented epitaxial L1 0 -FeNi films were fabricated by annealing the FeNiN films in a H 2 gas atmosphere at 300 C. S and K u of the denitride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, the primary issue with non-RE PMs is that they either possess high coercivity μ 0 H c or high saturation magnetization μ 0 M s . The origin and enhancement of the MAE in FeNi have been the subject of quite a few investigations [24,31,34,35]. Alternate monatomic layer deposition of FeNi has magnetic anisotropy of 0.7 MJ m −3 with 0.48 degree of order, as demonstrated by Kojima et al [21,36] and magnetic anisotropy has been shown to be closely related to the degree of order.…”
Section: Introductionmentioning
confidence: 96%
“…However, the primary issue with non-RE PMs is that they either possess high coercivity μ 0 H c or high saturation magnetization μ 0 M s . The origin and enhancement of the MAE in FeNi have been the subject of quite a few investigations [24,31,34,35]. Alternate monatomic layer deposition of FeNi has magnetic anisotropy of 0.7 MJ m −3 with 0.48 degree of order, as demonstrated by Kojima et al [21,36] and magnetic anisotropy has been shown to be closely related to the degree of order.…”
Section: Introductionmentioning
confidence: 96%
“…The ferromagnetic, ordered phase usually showed a high exchange-coupled interaction between the neighboring grains due to the large-grain growth during the thermal process. Thus, the nanocomposite and nanogranular ferromagnetic film structures fabricated at low-temperature conditions have attracted significant attention because of the decoupling of the intergranular interaction that could enhance the signal-to-noise ratio; therefore, they are considered more favorable for the next generation magnetic storage media [13][14][15][16][17][18][19][20][21][22][23]. Many attempts have been made to propose the effect of top or under layers; the additive effect of metal oxides and nitride elements is a successful method to control the chemical ordering, microstructure, magnetic coupling, and crystalline orientation of the L1 0 magnetic thin films to meet the requirements of industrial manufacture, especially in technologically important perpendicular magnetic materials for multifunctional device applications [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%